(untitled) (International Journal of Current Engineering and Technology, 2015)
Event based system are message passing systems in which its components are decoupled in nature. They separate the communication and computation, via an event notification service. Because of decoupled nature of these systems, it is necessary to analyze the performance of such systems in order to guarantee reliability and other Quality of Service (QoS) specifications. This paper mainly aims to carry out performance analysis to show the effects of enforcing QoS specification viz., latency, reliability and delivery semantics. The study is based on an event based system used to notify intended subscriber vehicles in case of traffic jams. Latency and reliability is derived with certain relations and delivery semantics is enforced while modeling the system. Stochastic Analysis, using Performance Evaluation Process Algebra (PEPA) is introduced to check the overall behavior of the system.